Video-assisted thoracoscopic anterior vertebral body tethering for the correction of adolescent idiopathic scoliosis of the spine. (17th May 2018) - Joshi, Vijay; Cassivi, Stephen D; Milbrandt, Todd A; Larson, A Noelle
Abstract: Adolescent idiopathic scoliosis affects children aged 11–18 years. Severe disease may necessitate spinal fusion. Vertebral body tethering gradually corrects scoliosis as the patients grow. The application of video-assisted thoracic surgery to the thoracic spine is a new area for further development.